Tantangan Regulasi Keuangan Bagi Perkembangan Perbankan Islam: - Selfi Afriani Gultom; Pandapotan Pandapotan; M. Shabri Abd. Majid; Marliyah Marliyah; Rita Handayani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The literature study of this article aims to analyze the challenges that must be considered by financial regulators, especially for Islamic financial institutions (Islamic banking). Literature study through content analysis by discussing the book Intermediate Islamic Finance by Nabil Maghrebi, Abbas Mirakhor, and Zamir Iqbal Wiley publisher in 2016 and 30 articles from emerald and direct science publisher which is the world's best journal publisher with a scopus index. The results of the content search found seven challenges in financial regulation, namely the calculation of profit and loss sharing (PLS) still referring to the interest system, the practice of implementing contracts overshadowed by conventional contracts, capital and minimum liquidity regulations still referring to general regulations, regulatory indicators in assessing efficiency still referring to in the general (conventional) model, weakness of regulations requiring Islamic financial institutions in and supervision, weakness of regulatory control in implementing good corporate governance, weaknes of sharia law courts dealing with violations of sharia law. Financial regulations have not fully sided with Islamic banking (sharia). Financial regulations must continue to be adjusted and rearranged so that Islamic banking can develop and develop in a healthy manner with conventional banking and be resilient in the face of crises. Key words : challenges, finance regulation, islamic banking